Social conditioning and deviant behaviour - Mukhopadhyay, Lipi (2002)
Human behaviour is conditioned by a number of factors. However, personality, attitudes and deviant behaviour are results of many socio-psychological and biological factors. Over the years sociologists and psychologists have argued on the behaviours being conditioned genetically or socially. Inherent differences among human beings interact to produce such complex traits and abilities as are manifested in intelligence and personality, in mental illness and criminality. The early socialisation process is very important for shaping human behaviours. Discipline helps in building moral code, rewards, punishments, development of conscience, family relationships, personality development and personality changes in late childhood. The article deals with the factors that formulate personality and social behaviour of people starting from the childhood. Those factors and human behaviours are interrelated to the core. The author explains how deviant behaviour in society as well as family is increasing due to lack of understanding or realisation of the interplay of these factors. - Reproduced.
Keywords: Human behaviour; Deviant behaviour; Social conflicts; Behaviour